2017 43rd Euromicro Conference on Software Engineering and Advanced Applications (SEAA) 2017
DOI: 10.1109/seaa.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Competitor Interaction on Startup’s Product Development

Abstract: Context and motivation] Due to lack of resources and teams with low levels of experience, startups face several challenges during their product development, such as product customization, attracting new customers, and mastering the technology uncertainty. To increase their market presence and compensate for their lack of resources, startups need to consider other options such as joint ventures and partnerships.[Question/problem] Some companies that share highly similar resources and businesses can be potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It has been observed that the RE process is of significant interest in small software companies [6] and software startups because it is central to their software engineering activities [7]. Our previous research [29,30] on this topic explored the effect of competitor's interaction during the process 90 and identified the following most commonly used techniques during RE processes: internal sources (e.g., for requirements sources); analyses of similar products (e.g., elicitation of requirements); the use of informal notes (e.g., for requirements specification); identifying value for customers, products, and 95 stakeholders (e.g., for requirements prioritization); and internal reviews/prototypes (e.g., for validation of the requirements). Melegati et al in [31] interviewed representatives of software startups and found that external factors, such as the startup ecosystem, founders, team, and market, affect the RE process.…”
mentioning
confidence: 99%
“…It has been observed that the RE process is of significant interest in small software companies [6] and software startups because it is central to their software engineering activities [7]. Our previous research [29,30] on this topic explored the effect of competitor's interaction during the process 90 and identified the following most commonly used techniques during RE processes: internal sources (e.g., for requirements sources); analyses of similar products (e.g., elicitation of requirements); the use of informal notes (e.g., for requirements specification); identifying value for customers, products, and 95 stakeholders (e.g., for requirements prioritization); and internal reviews/prototypes (e.g., for validation of the requirements). Melegati et al in [31] interviewed representatives of software startups and found that external factors, such as the startup ecosystem, founders, team, and market, affect the RE process.…”
mentioning
confidence: 99%
“…In certain cases, a study of the competition can serve as a good starting point for the conception of solutions [72]. A study of the competition can also help the startup to recognize the best time to perform a pivot [73], as well as potential partnerships into which they can enter [74]. However, in the current context, the central aim of this study of the competition is to contrast the current offerings with that of the competition, to improve the current offering by determining the base set of features and establishing a relevant USP.…”
Section: Stage 6: Studying the Competitionmentioning
confidence: 99%
“…These were concept, development, working prototype, functional product with limited users, functional product with high growth, and mature product. Moreover, our earlier studies on software startups simply explored the effects of competitor interactions on product development and product 60 idea validation [18,19].…”
Section: Software Startup and Product Developmentmentioning
confidence: 99%
“…To find the articles, keywords related to population and intervention were used (Table 2). Keywords used for population were taken from a previous study ( [25]), while keywords for intervention were based on the learning gained during our previous work [18]. In that study, we conducted an experiment on the RE process in software startups.…”
Section: Literature Search Strategymentioning
confidence: 99%